The Implementation of Multicultural Values in Arabic Learning - Amrina Amrina; Zulmuqim Zulmuqim; Iswantir Iswantir; adam mudinillah; Ahmad Firdaus Mohd Noor (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
The purpose of this study is to describe and analyze multicultural values in Arabic language learning in Madrasah (school) and what are the obstacles for educators in undergoing multiculturalism. The method used in this research is qualitative, with a field research study done in a detailed, intensive, and profound way on the object under investigation. The data analysis technique used is content analysis and descriptive analysis. The results of this study explain that the implementation of multicultural values in Arabic lessons in Madrasah has the values of democracy, humanism, and tolerance so that students can learn Arabic among their friends without the need to look at ethnicity, race, or culture. The challenges and obstacles in carrying out multiculturalism are the adaptation of students to the introduction of the learning environment, the understanding of which has not led to the value of diversity. With multicultural values, tolerance and mutual respect create a conducive and fun learning atmosphere so that learning Arabic does not become a realm of fear for students.